Gardner syndrome associated with multiple osteomas, intestinal polyposis, and epidermoid cysts - Koh, Kwang-Joon; Park, Ha-Na; Kim, Kyoung-A (Imaging science in dentistry, 2016)
Gardner syndrome is known as a variant of familial adenomatous polyposis. This syndrome is characterized by multiple intestinal polyposes, osteomas, and epidermoid cysts. In addition, dental abnormalities include an increased frequency of multiple odontomas, as well as supernumerary and impacted teeth. The authors report the case of a 7-year-old male patient with Gardner syndrome. Radiographic findings revealed multiple osteomas in both sides of the maxilla, multiple diffuse enostoses in both jaws, and a complex odontoma in the left mandibular body. Two years later, multiple epidermoid cysts on the scalp were found. Since this patient was suspected to have Gardner syndrome, the authors recommended gastrointestinal endoscopy to check for intestinal polyposis. Gastrointestinal endoscopic examination revealed multiple polyposes in the upper gastrointestinal tract and fundus of the stomach. As a result, the final diagnosis was Gardner syndrome.